Monitoring Tekanan Darah Pada Pasien Diabetes Melitus Tipe Dengan Hipertensi Di Puskesmas Tlogosari Kulon Kota Semarang - Fef Rukminingsih; Putri Sri Wahyuni (Journal Clinical Pharmacy and Pharmaceutical Science, 2023)
Diabetes Mellitus (DM) is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action, or both. DM is a risk factor for hypertension. Hypertension in DM increases the risk of complications so it is necessary to monitor whether blood pressure targets are achieved. This study aims to determine the achievement of blood pressure targets in type 2 DM patients with hypertension at the Tlogosari Kulon Health Center, Semarang City. This research is a descriptive observational study. Data collection uses purposive sampling technique. Data were obtained from medical records of type 2 DM patients with hypertension aged ≥ 45 years, who had blood pressure examination results on 2 consecutive visits in September 2022 – February 2023, use antihypertensives for at least 1 year. It was found 47 patients, consisting of 25 male patients and 22 female patients. A total of 26 patients were aged between 60-69 years. A total of 36 patients (76.59%) had taken antihypertensives for 1-5 years and 42 patients (89.40%) received single therapy, namely amlodipine. Only 1 patient received combination therapy of 2 drugs (amlodipine and candesartan). There were 14 patients who achieved the target blood pressure <140/90 mmHg (29.78%).